Marketing Communication Strategy of Pandayangan Tourism Ulumahuam Village in Labuhan Batu Selatan Regency in Improving Tourism Visit - Annisa Damayanti; Abdul Rasyid (PT Mattawang Mediatama Solution, 2022)
Pandayangan Tourism is a natural tourist destination with a flowing river and beautiful natural surroundings, and it works in collaboration with the Labusel children's community. The study's goal was to identify and analyze Pandayangan tourism through the use of a Marketing Communication Strategy to Increase Tourist Visits. This study employs a descriptive qualitative approach, with data gathered through interviews with tourism managers, observations, and literature searches. Integrated Marketing Communication is the theory employed (IMC). Based on the data analysis, it was determined that Pandayangan Tourism had implemented a marketing strategy during the promotion stage, which was accomplished by using mass selling and public relations methods, understanding the benefits and drawbacks of tourism products, and carrying out marketing objectives that emphasized increasing sales in order to increase visitors. Pandayangan tourism's marketing strategy activities include providing the best facilities for the convenience of visitors. Promotional activities, understanding the benefits and drawbacks of tourism products, and achieving marketing objectives are all concluded to always obtain and produce an increase in visitors.